Adakah Halo Effect Terhadap Profesi Guru: Pengetahuan Karier Dan Ekspektasi Mahasiswa Calon Guru Terhadap Profesi Guru - Deis Linda; Vera Ariyanti; Wily Ferdiansyah; Adhira Hildan Fajrian; Anggi Bagus Febrian; Eko Sujarwanto (Jurnal Studi Guru dan Pembelajaran, 2024)
Education is a fundamental foundation in the development of society and the nation. In the educational process, teachers play an important role in shaping the younger generation to support a nation's quality human resources. However, prospective teachers in Indonesia currently face various challenges and high expectations. Society's expectations of teachers as agents of change in the educational process often exceed the understanding and readiness of prospective teacher students. This is further exacerbated by the recent phenomenon of the hashtag #JanganJadiGuru on Platform X, highlighting concerns related to demands for fair salaries, proportional teacher workloads, and appropriate recognition. Adequate knowledge about the teaching profession and a realistic understanding of the expectations that prospective teacher students will face are crucial. However, in reality, prospective teachers' knowledge about the teaching profession, requirements, and professional expectations is often limited or inaccurate, affecting the learning process. The purpose of this research is to investigate the career knowledge of prospective teacher students and their expectations towards the teaching profession. This research was conducted in the city of Tasikmalaya with the research subjects being prospective teacher students, with respondents consisting of 27 from Universitas Siliwangi, 17 from Universitas Perjuangan, 21 from Universitas Pendidikan Indonesia, and 11 from Universitas Muhammadiyah Tasikmalaya, making a total of 76 respondents. In this research, the researcher used a quantitative approach supported by a qualitative approach. Based on the conducted research, we can state that there is a significant possibility of a halo effect on the teaching profession. The positive image associated with the teaching profession, such as being unsung heroes, nation character builders, and pillars of education, tends to create high expectations for this profession. However, behind these positive aspects, there are also complex realities and significant challenges.